2006
DOI: 10.1158/1535-7163.mct-05-0317
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of bryostatin 1 and 12-O-tetradecanoylphorbol-13-acetate on the regulation and activation of RasGRP1 in mouse epidermal keratinocytes

Abstract: The antitumor agent bryostatin 1 and the tumorpromoting phorbol esters function as structural mimetics of the second lipid messenger diacylglycerol (DAG) by binding to the C1 domain of DAG receptors. However, bryostatin 1 and the phorbol esters often differ in their cellular actions. In mouse skin, the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) is a potent tumor promoter, whereas bryostatin 1 lacks this activity and antagonizes the tumor-promoting effects of TPA. Although protein kinase C mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Closer examination of the keratinocytes showed cytoplasmic and perinuclear localization of RasGRP1 in the cells (Fig. 3C), a localization that matched the subcellular distribution of RasGRP1 in keratinocytes in culture (8,10).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Closer examination of the keratinocytes showed cytoplasmic and perinuclear localization of RasGRP1 in the cells (Fig. 3C), a localization that matched the subcellular distribution of RasGRP1 in keratinocytes in culture (8,10).…”
Section: Resultssupporting
confidence: 54%
“…We have recently shown that the Ras exchange factor and phorbol ester receptor RasGRP1 is expressed in mouse primary keratinocytes, where it mediates Ras activation in response to the tumor-promoting phorbol ester TPA (8,10). To explore in more detail the role of RasGRP1 in the epidermis and in tumor promotion, we generated a transgenic mouse model in which overexpression of RasGRP1 was targeted to the basal layer of epidermal keratinocytes and the outer root sheath of hair follicles using the bovine K5 promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that transient overexpression of RasGRP1 in primary keratinocytes in vitro causes Ras activation and that TPA further increases it (13,14). To test whether keratinocytes derived from K5.RasGRP1 mice were also more sensitive to the TPA-mediated activation of Ras than the wild-type cells, we measured the levels of active, GTPbound Ras using a pull-down assay in keratinocytes derived from both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Levels of GTP-loaded Ras (Ras GTP ) were measured by using the GST-RBD domain of Raf-1 as a probe in an affinity precipitation or pull-down assay. Briefly, primary keratinocytes were first isolated from K5.RasGRP1 or wild-type mice as described elsewhere (14). Cells were serum starved overnight, treated with vehicle (Me 2 SO) or 1 Amol/L of TPA for 15 min, and harvested on ice in lysis buffer containing 25 mmol/L Tris-HCl (pH 7.5), 150 mmol/L of NaCl, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation